Implementasi Pengembangan Anak Usia Dini Holistik Integratif di Kota Balikpapan Provinsi Kalimantan Timur tahun 2022 - Heppy Liana; Hasbi, Sjamsir; Rusnaida; Ummah, Nursalimil (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
Holistic-Integrative Early Childhood Development (PAUDHI) is an early childhood development effort undertaken to meet the diverse and interrelated essential needs of children simultaneously, systematically, and integrated Ly. Includes education, health, nutrition, care, care, protection and welfare services. (PERPRES Number 60 of 2013). Formulation of the problem: 1) How is the implementation of HI ECD in Balikpapan city? 2) What are the obstacles faced in implementing HI ECD?, 3) What are the solutions in implementing HI ECD. The results of the study 1) The 2022 HI ECD implementation in Balikpapan City, East Kalimantan Province was carried out well and smoothly. The Balikpapan Office has carried out BIMTEK HI PAUD HI to 100 PAUD managers and PAUD teachers in Balikpapan city and the technical guidance participants are required to carry out an imitation of the 10 nearest PAUD units 2) obstacles encountered: a) PAUD units do not yet have a curriculum that is integrated with the implementation of PAUD HI. b) Collaboration with elements of partners and OPD has not been supported by a cooperation agreement. c) Activities involving parents in the unit have been carried out, although not all of them have been carried out considering that learning activities have only started to be active again after the pandemic period (Online 2 years). 3) efforts to overcome obstacles in implementing HI PAUD in Balikpapan city a) Prepare a plan to increase the competence of educators and related education personnel to develop HI PAUD-based curriculum together with the Education Office and PAUD Units, b) Make a cooperation agreement/MOU with Local Government Organizations (OPD) smart one. C) Designing activities with parents, Conclusion the PAUD unit in Balikpapan has implemented PAUD HI services including as a liaison for various services to fulfil children's essentials, OPD involvement has been carried out but some units have not collaborated with the population and civil registration services because the NIK requirements have been met. PAUD units are forced to accept children with special needs (ABK), who are only found out when they start learning. Some PAUD Units already have a follow-up program on students' health checks with the involvement of parents.